Service Quality Influence on Repurchase Intention, Through Customer Satisfaction Mediation: Indonesia Music Studio Perspective - Pranoto, Henry; Soetedja, Venny; Paramitha, Teta Maharani; Wibowo, Analicia (Jurnal Aplikasi Bisnis dan Manajemen, 2023)
The research purpose is to find significant effect of service quality (tangible, reliable, responsiveness, assurance, and empathy) on repurchase intention, through intervening variable of customer satisfaction at Bumi Musik Gemilang (BMG) recording studio, Malang-Indonesia. This quantitative research applies JASP software, an open-source statistics program, to process the questionnaires research data. The research participants consist of 169 respondents who are customers of BMG Music Recording Studio. The results show that the five dimensions of service quality have a significant effect on customer satisfaction. Meanwhile, the dimensions of service quality that have a significant effect on repurchase intention through the mediation of customer satisfaction are reliability and empathy. However, the variable customer satisfaction does not show a mediating effect on the relationship between the dimensions of tangible, responsiveness and assurance on repurchase intention. Customer satisfaction has a significant effect as an intervening variable between service quality and repurchase intention. Keywords: customer satisfaction, Indonesia, music recording studio, repurchase intention, service quality